2022
DOI: 10.3390/en15041294
|View full text |Cite
|
Sign up to set email alerts
|

Load Estimation for Induction Heating Cookers Based on Series RLC Natural Resonant Current

Abstract: In domestic induction heating applications, cookware can be considered an equivalent load in a series resistor–inductor–capacitor resonant converter. Therefore, the electrical parameters of an equivalent circuit change according to the cookware material, size and the cookware position on the heating coil. This study proposes an online estimation method for detecting the cookware status, determining the material and estimating the equivalent heating resistance of cookware on an induction heating cooker (IHC) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…However, while in more complex resonant inverters, the current in the resonant tank is managed by the control strategy of two or more switches, allowing an efficient control in the desired frequency range, in a singleswitch inverter the design of the converter has to be tightly coupled with the analysis of the coil-workpiece system. Finally, some direct online load identification techniques have been developed to evaluate the load in real induction heating systems with full-bridge or half-bridge inverters [10,11]. Still, these methods require to process current measurements in real time, augmenting the complexity of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, while in more complex resonant inverters, the current in the resonant tank is managed by the control strategy of two or more switches, allowing an efficient control in the desired frequency range, in a singleswitch inverter the design of the converter has to be tightly coupled with the analysis of the coil-workpiece system. Finally, some direct online load identification techniques have been developed to evaluate the load in real induction heating systems with full-bridge or half-bridge inverters [10,11]. Still, these methods require to process current measurements in real time, augmenting the complexity of the systems.…”
Section: Introductionmentioning
confidence: 99%
“…As examples of circuit design and analysis studies, references [3], [8], [12], [18]- [22] can be cited. And also in the literature, numerous studies can be found that examine the effects of the pot used in induction heating cookers on the resonant circuit Almost all these studies explain the relationship between the pot and the coil using modeling methods resembling an R-L circuit [11], [14], [23]- [27]. As a result of the studies in the literature, parameters such as the pot diameter, pot material, the operating frequency of the resonant circuit, and the pot's position on the coil are highlighted as factors that should be taken into consideration during the design phase.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, these values are subject to variations based on factors such as the operating frequency of the resonant circuit, ambient temperature, and air gap between the pan and the coil. As a result, there exists a wide range of academic research focusing on pan and load recognition [11,29,[33][34][35][36]. However, the design of the coil itself necessitates a comprehensive academic investigation.…”
Section: Introductionmentioning
confidence: 99%